El Caso Belaochaga (1907): Represión policial y representación periodística de la homosexualidad masculina en Lima - Velázquez Castro, Marcel (Anuario de Historia de América Latina, 2020)
This article studies the first modern case of police repression against male homosexuals in the city of Lima. The Belaochaga Case (1907) allows us to understand, on one side, the logic of control and police repression, the legal order and penal laws against sodomy and, on the other side, the representation of this news and its effects on the illustrated magazine Fray K.Bezón, which combined popular humour and innovative forms of mass culture sensationalism. This article presents three approaches. Firstly, it analyzes the decline of the traditional representation of the so-called “fag”, as an afrodescendant subject and social outcast in Lima. Secondly, it describes the narrative and visual construction of a transvestite homosexual collective that exhibited themselves through photographs creating in this way a new social type, object of mockery in the Fray K.Bezón magazine. Thirdly, it highlights the relevance of criminal law discourse and the police repression of urban homosexuals.